Review of disability evaluation study design : third interim report - Wunderlich, Gooloo S.; Kalsbeek, William D., 1946- (National Academy Press, 1999)
The Social Security Administration (SSA) has been engaged in a major effort to redesign the process for determining disability for cash benefits and medical assistance under its Social Security Disability Insurance (SSDI), Title II of the Social Security Act and the Supplemental Security Income (SSI), Title XVI of the Social Security Act. Because of the complexity and far-reaching impact of its efforts, SSA concluded that the redesign effort requires extensive research, testing, and validation, as well as further development of some of its components before national implementation. The effect of the new determination process on the number and characteristics of future beneficiaries also needs further study. The agency asked the National Academies to provide ongoing independent and unbiased review of, and recommendations on, its current and proposed research as it relates to the development of a revised disability decision process including the approach, survey design, and content of the complex multiyear Disability Evaluation Study (DES). The present report is the third in a series of short interim reports of the National Academies' Committee to Review the SSA's Disability Decision Process. This third interim report relates directly to one of the contract tasks-review of the design, approach, and content of the DES, as proposed by SSA's contractor for the survey, Westat, Inc. This report is limited to a brief review of the sample design (including that of the pilot study), instruments and procedures, and response rates goals developed by Westat and provided by SSA in June 1999 to the committee for its review and recommendations. It also comments on the proposed timeline for initiation of each phase of the survey.